2020
DOI: 10.1523/eneuro.0423-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic Inhibition of Infralimbic Prefrontal Cortex GABAergic Parvalbumin Interneurons Attenuates the Impact of Chronic Stress in Male Mice

Abstract: Hypofunction of the prefrontal cortex (PFC) contributes to stress-related neuropsychiatric illnesses. Mechanisms leading to prefrontal hypoactivity remain to be determined. Prior evidence suggests that chronic stress leads to an increase in activity of parvalbumin (PV) expressing GABAergic interneurons (INs) in the PFC. The purpose of the study was to determine whether reducing PV IN activity in the Infralimbic (IL) PFC would prevent stress-related phenotypes. We used a chemogenetic approach to inhibit IL PFC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 82 publications
2
16
0
1
Order By: Relevance
“…Created with BioRender.com. (Nawreen et al, 2020). Furthermore, chronic stress increases GAD67 mRNA in the male mouse IL (Shepard et al, 2016).…”
Section: Chronic Stress Impactsmentioning
confidence: 96%
“…Created with BioRender.com. (Nawreen et al, 2020). Furthermore, chronic stress increases GAD67 mRNA in the male mouse IL (Shepard et al, 2016).…”
Section: Chronic Stress Impactsmentioning
confidence: 96%
“…Nonetheless, low doses of CNO (≤3 mg/kg bodyweight) are reported to result in subthreshold clozapine concentrations that are unlikely to bind with endogenous receptors, as the affinity of clozapine for DREADDs is much higher [ 14 , 17 , 18 , 19 ]. Although many studies demonstrated the absence of behavioral off-target effects induced by CNO or back-metabolized clozapine in animals without DREADD expression [ 20 , 21 , 22 , 23 , 24 , 25 ], other ligands have been developed to overcome this concern—e.g., olanzapine [ 26 ], perlapine [ 27 ], compound 21 [ 27 ], deschloroclozapine [ 28 ], and JHU37160/152 [ 29 ] ( Figure 1 e). The absence of off-target effects of these new generation of DREADD actuators also remains to be demonstrated.…”
Section: Dreaddful Hurdles In (Chronic) Chemogenetic Studiesmentioning
confidence: 99%
“…This is underscored by studies comparing results obtained from acute and chronic DREADD applications. Although some of those experiments show a similar level of neuronal activity or behavioral outcomes [ 22 , 49 ], many others report null or antagonistic effects upon continuous DREADD activation [ 21 , 22 , 23 , 36 , 37 , 38 , 41 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] ( Table 1 ). Given these discrepancies, it is clear that there is no straightforward way to extrapolate study results of acute experiments to chronic experiments and more fundamental knowledge of chronic neuromodulation is of key importance.…”
Section: Dreaddful Hurdles In (Chronic) Chemogenetic Studiesmentioning
confidence: 99%
“…Chronic treatment with escitalopram did not modify the neurogenic and behavioral changes observed in these animals. Considering that parvalbumin (PV) interneurons in the prefrontal cortex are also capable of modulating depressive-and anxiety-like behaviors (Fogaça et al, 2020;Nawreen et al, 2020;, we decided to investigate the impact of iNOS deletion in another region and cell population associated with these changes. We observed that neither PV density nor their recruitment was affected by our manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, também foi demonstrado que a estimulação elétrica subconvulsivante do PrL evoca respostas de enfrentamento ativo no FST em uma linhagem de ratos depressivos (DRL-do inglês "depressive rat line"). Dessa SIERRA- MERCADO et al, 2011;NAWREEN et al, 2020).…”
unclassified